2001
DOI: 10.1002/1097-4644(20010401)81:1<149::aid-jcb1031>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

5?UTR sequences of the glucocorticoid receptor 1A transcript encode a peptide associated with translational regulation of the glucocorticoid receptor

Abstract: We have recently reported that glucocorticoid receptor (GR) transcript 1A, one of the five mouse GR splice variants (1A-1E), encodes membrane GR (mGR), which subsequently participates in mediating the apoptotic effects of glucocorticoids (GCs); all transcripts vary at their 5'UTR. Computer analysis of the entire1026 bp comprising the 5'UTR of transcript 1A identified five putative translation start sites at positions 85, 217, 478, 628, and 892 with the potential to encode peptides of 33, 93, 6, 18, and 41 amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 30 publications
(48 reference statements)
1
29
0
Order By: Relevance
“…This means that there are potential short coding regions in the 5Ј-UTRs of many genes if this classical model, indeed, represents a general mechanism of translation initiation. To our knowledge, few reports have presented evidence of the translation of upstream ORFs in vivo (Diba et al 2001). Although there are also some mechanisms by which the ribosomal complex may evade the translation from the first ATG codon, such as leaky scanning (Kozak 1999) and IRES (internal ribosome entry site)-dependent translation (Meijer and Thomas 2002), we expect that the small proteins encoded by upstream ORFs in 5Ј-UTRs exist in vivo.…”
Section: National Institute Of Advanced Industrialmentioning
confidence: 96%
“…This means that there are potential short coding regions in the 5Ј-UTRs of many genes if this classical model, indeed, represents a general mechanism of translation initiation. To our knowledge, few reports have presented evidence of the translation of upstream ORFs in vivo (Diba et al 2001). Although there are also some mechanisms by which the ribosomal complex may evade the translation from the first ATG codon, such as leaky scanning (Kozak 1999) and IRES (internal ribosome entry site)-dependent translation (Meijer and Thomas 2002), we expect that the small proteins encoded by upstream ORFs in 5Ј-UTRs exist in vivo.…”
Section: National Institute Of Advanced Industrialmentioning
confidence: 96%
“…There are even examples of canonical non-coding RNAs, such as pri-miRNAs [66] and ribosomal RNAs [67][68][69], encoding biologically active peptides with well characterised functions. Similarly some uORFs have been shown to exert their regulatory function through their encoded peptides, with this regulation depending on their aa sequence [70], and being able to occur in trans [71][72][73][74].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…A variety of different 5 ¶ sequences may influence post-transcriptional gene processes, such as mRNA processing, export, and stability. It has also been suggested that promoter usage may regulate the differential response of GR expression to glucocorticoids (23), the expression of specific membrane or intracellular receptor isoforms (24), or even direct GR mRNA translation (25).…”
Section: Introductionmentioning
confidence: 99%